OVERALL AND CANCER-SPECIFIC SURVIVAL OF HIGH-RISK PROSTATE CANCER - IMPACT OF ADJUVANT THERAPY AFTER RADICAL PROSTATECTOMY - Tosho Ganev (Peytchinski Publishing, 2023)
Purpose: The study examines the survival of patients with high-risk prostate cancer in order to find a relationship between survival and the type of postoperative therapy. Materials/Methods: The object of the study were 872 patients who underwent radical prostatectomy in the Clinic of Urology in "St. Anna - Varna" Hospital for the period from April 17, 1996, until November 25, 2022. Postoperatively, some patients were additionally subjected to hormonal therapy (referred to as "dual therapy" in the text), and others to hormonal and radiotherapy (referred to as "triple therapy"). Results: Overall and cancer-specific survival of high-risk patients did not differ statistically significantly for the two types of postoperative therapy. Conclusions: The optimal combination of radical prostatectomy, hormonal and radiotherapy in order to achieve maximum survival for patients with high-risk prostate cancer is still poorly defined.